Mental health problems and suicidal expressions among young male prisoners in Cambodia: a cross-sectional study - Puthy Pat; Linda Richter-Sundberg; Bhoomikumar Jegannathan; Kerstin Edin; Miguel San Sebastian (Taylor & Francis Group, 2021)
Background incarceration and mental health problems are known to have a strong empirical association. Many studies have confirmed the high prevalence of mental health problems among young prisoners in particular, yet none has been conducted in Cambodia. Objectives this study aimed to assess the level of mental health problems and suicidal expressions, and determine the associated risk factors among young prisoners in Cambodia. Method this was a cross-sectional study among 572 young prisoners between the ages of 15 and 24 from three prisons. Sociodemographic data and detailed information on participants' profiles were gathered, and mental health problems and suicidal expressions were assessed using the Youth Self-Report (YSR) and the Attitude Towards Suicide (ATTS) questionnaires, respectively. Results Mental health problems as revealed by the mean YSR scores were: 25.97 for internalizing and 18.12 for externalizing problems; 11.88 for anxiety/depression, 9.97 for aggressive behaviours and 7.53 for somatic complaints. Social problems, attention problems and rule breaking behaviour were in the range of 8.10 to 8.49. Withdrawal depression and thought problems mean scores were 6.55 and 6.66, respectively. Mental health problems were associated with younger age, lower educational background, and shorter duration of incarceration. Around 16% had thought about their own death, and 12% expressed wish to die. Suicide ideation, planning, and attempts were reported by almost 7%, 2%, and 3% of participants respectively. Prior drugs users thought about death significantly more than their counterparts while suicide ideation was significantly lower among prisoners with higher education. Conclusion Mental health problems and suicidal expressions among young prisoners warrant well-planned mental health services that are integrated into the current prison health system. A contextualised intervention that takes into account age, education, duration of incarceration and previous drug use may contribute to improve the mental well-being of young prisoners in Cambodia.